2001
DOI: 10.1182/blood.v97.1.312
|View full text |Cite
|
Sign up to set email alerts
|

Lutheran blood group glycoprotein and its newly characterized mouse homologue specifically bind α5 chain-containing human laminin with high affinity

Abstract: Lutheran blood group glycoproteins (Lu gps) are receptors for the extracellular matrix protein, laminin. Studies suggest that Lu gps may contribute to vasoocclusion in sickle cell disease and it has recently been shown that sickle cells adhere to laminin isoforms containing the ␣5 chain (laminin 10/11). Laminin ␣5 is present in the subendothelium and is also a constituent of bone marrow sinusoids, suggesting a role for the Lu/ laminin interaction in erythropoiesis. The objectives of the current study were to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
105
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 35 publications
5
105
0
Order By: Relevance
“…On the other hand, sol-Lu did not bind to laminin-1 (␣1␤1␥1). This specificity for laminins containing the ␣5 chain is consistent with published results (20,27). We therefore conclude that sol-Lu has binding properties similar to native cell surface Lu and is an appropriate tool to investigate and identify Lu-binding sites on the laminin ␣5 chain.…”
Section: Production Of Recombinant Sol-lu Protein and Its Binding Tosupporting
confidence: 77%
See 2 more Smart Citations
“…On the other hand, sol-Lu did not bind to laminin-1 (␣1␤1␥1). This specificity for laminins containing the ␣5 chain is consistent with published results (20,27). We therefore conclude that sol-Lu has binding properties similar to native cell surface Lu and is an appropriate tool to investigate and identify Lu-binding sites on the laminin ␣5 chain.…”
Section: Production Of Recombinant Sol-lu Protein and Its Binding Tosupporting
confidence: 77%
“…Udai et al (25) demonstrated that the major laminin receptor present on sickle cells is the Lu/B-CAM protein. Furthermore, K562 cells transfected with human Lu adhere to laminin-10/11 but not to laminins lacking the ␣5 chain (27). In our previous studies we made an antibody specific for mouse Lu, and we determined its expression pattern (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At least some studies have shown that B-CAM/LU is associated with the cytoskeleton in red blood cells [17], making our hypothesis a reasonable one to explore. Therefore, to determine if the cytoskeleton is involved in regulation of B-CAM/LUmediated cell adhesion to laminin, we performed adhesion studies under both static and continuousflow conditions using MEL cells expressing B-CAM with a cytoplasmic tail truncated to five amino acids (B-CAM-ST5/MEL).…”
mentioning
confidence: 92%
“…The red cell laminin receptor B-CAM/LU [15] is the protein that bears Lutheran blood group antigens and binds specifically to laminins containing the a5 chain (laminins 10 and 11) [16,17]. B-CAM/LU comprises two protein spliceoforms derived from a single gene; B-CAM lacks the last 40 cytosolic amino acids of the LU protein [18,19].…”
Section: Introductionmentioning
confidence: 99%